Knowledge of pregnant women on the factors that influence anaemia in pregnancy in a rural farming district of the Western Region of Ghana - Konlan, Kennedy D.; Amoah, Roberta M.; Saah, Joel A.; Abdulai, Juliana A.; Mohammed, Iddrisu; Konlan, Kennedy Dodam; Doat, Abdul Razak (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The presence of anaemia in pregnancy is one of the serious public health concerns across the globe especially in developing countries like Ghana. This study assessed pregnant women’s knowledge on factors influencing aneamia in pregnancy in a low-income district of Ghana. Methods: A quantitative descriptive cross-sectional study. Data was collected using a pretested questionnaire. 112 pregnant women seeking antenatal care were recruited using systematic sampling technique in the Wassa East district of Ghana. Data were cleaned and entered into SPSS version 22 and analysed into descriptive statistics. Results: Majority of participants; 72.3% did not know the causes of anaemia in pregnancy. Pregnant women (27.7%) indicated nutritional deficiency as a common cause of anaemia; 18.7% of them could identify appropriately at least one sign of anaemia in pregnancy with 28% asserting that pregnancy-related anaemia can affect labour, despite 72% indicating that anaemia could cause maternal mortality. The reasons for irregular ANC attendance included; perceived non importance of ANC (18.8%), financial difficulties (17.9%), health facility inaccessibility (18.8%) and time constraints (44.5%). There was a strong association between knowledge level on the cause of anaemia in pregnancy and the educational level of pregnant women (p=0.005 chi square = 50.289). Conclusions: Lack of knowledge on the importance of antenatal care and financial constraints were among the reasons leading to a surge in anaemia amongst pregnant women in the district. Health providers should incorporate services which enable pregnant women to access valuable information on anaemia prevention in pregnancy.